Ideology-Driven Telecommunications Market Leads to a Second-Rate Outcome - Gregory, Mark A (Journal of Telecommunications and the Digital Economy, 2020)
Papers in the December 2020 issue of the Journal include a discussion about the parlous state of television broadcasting in Australia, 6G and the future of the National Broadband Network. The digital economy is a focus, with papers on tax risk assessment and assurance and the use of e-commerce by MSEs in Indonesia. Global telecommunications markets are struggling to move beyond the 20th century thinking and ideology-driven decision making that pervades many governments. Telecommunications use has surged as work from home has become normalised, yet the digital divide and second-rate outcomes abound as the result of poor decision making by government. Dr Leith Campbell takes over as the Managing Editor in January 2021. The Journal welcomes contributions on telecommunications and the digital economy.